Early identification of patients in need of palliative care in slovenian general practice - Klok Lisette; Engels Yvonne; Veldhoven Carel; Rotar Pavlič Danica (Sciendo, 2018)
To help general practitioners (GPs) in early identification of patients with palliative care (PC) needs, this pilot study aimed to determine the potential of the combined original surprise question (SQ1) ('Would I be surprised if this patient died within the next 12 months?') and the second surprise question (SQ2) ('Would I be surprised if this patient was still alive after 12 months?'). We hypothesized that answering these SQs would trigger them to make a multidimensional care plan.